Effectiveness of Digital Payments to Maintain Financial Portfolio Case Study of QRIS Bank Syariah Indonesia and Bank Muamalat - Widyaningsih, Bekti; Rahmatika, Arivatu Ni’mati; Pranata, Hendi Yoga (Formosa Journal of Sustainable Research, 2024)
Effectiveness is a measure that states how far a program in terms of quality, quantity and time has achieved its goals. The purpose of this study is to analyze how the effectiveness of digital payments increases the financial portfolio of Islamic banking and the influence of digital payment QRIS and the right strategy to take advantage of QRIS implementation opportunities in Islamic banks. The method used is qualitative with a descriptive approach. Data sources are primary and secondary data with interview and observation studies. The results of the study show that Bank Syariah Indonesia (BSI) and Bank Syariah Muamalat have a significant influence in increasing transaction efficiency, expanding reach, transaction speed. Strategies to overcome implementation opportunities by building customer trust, transaction security and cost transparency. Research data to observe the effectiveness of QRIS to maintain the financial portfolio of Islamic banking